2020
DOI: 10.1186/s12866-020-1699-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of endocrine disruptor Bisphenol A by Pseudomonas putida strain YC-AE1 isolated from polluted soil, Guangdong, China

Abstract: Background: Bisphenol A is an important organic chemical as an intermediate, final and inert ingredient in manufacturing of many important products like polycarbonate plastics, epoxy resins, flame retardants, fooddrink packaging coating, and other. BPA is an endocrine disruptor compound that mimics the function of estrogen causing damage to reproductive organs. Bacterial degradation has been consider as a cost effective and eco-friendly method for BPA degradation compared with physical and chemical methods. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Bisphenol A (BPA) is widely used in the manufacture of synthetic resin, plastics, polycarbonates and other products [1], and is also a well-known pollutant that shows estrogenic and mutagenic effects and acute toxicity [2]. Due to its low cost and increased environmentally friendliness when compared to physical and chemical methods, bioremediation of BPA has proved to be a promising method in recent years [3]. Several species of BPA-degrading bacteria have been reported, including Achromobacter xylosoxidans [4], Bacillus cereus and Bacillus megaterium [1, 5], Cupriavidus basilensis [6], Sphingobium bisphenolivorans [7], Sphingomonas bisphenolicum [8], Pseudomonas putida [3, 9], and so on.…”
Section: Full-textmentioning
confidence: 99%
“…Bisphenol A (BPA) is widely used in the manufacture of synthetic resin, plastics, polycarbonates and other products [1], and is also a well-known pollutant that shows estrogenic and mutagenic effects and acute toxicity [2]. Due to its low cost and increased environmentally friendliness when compared to physical and chemical methods, bioremediation of BPA has proved to be a promising method in recent years [3]. Several species of BPA-degrading bacteria have been reported, including Achromobacter xylosoxidans [4], Bacillus cereus and Bacillus megaterium [1, 5], Cupriavidus basilensis [6], Sphingobium bisphenolivorans [7], Sphingomonas bisphenolicum [8], Pseudomonas putida [3, 9], and so on.…”
Section: Full-textmentioning
confidence: 99%
“…It has to be stressed that p -HAP can be formed from 1,2-bis(4-hydroxyphenyl)-2-propanol (Product 2, Scheme 1 ) as suggested in a number of papers [ 4 , 5 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 21 , 30 , 31 , 32 ]. Therefore, bio-oxidation of BPA into Product 2 in the environmental water is possible, however, Product 2 is immediately converted into p -HAP (most probably through 4,4′-dihydroxy-α-methylstilbene).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, bio-oxidation of BPA into Product 2 in the environmental water is possible, however, Product 2 is immediately converted into p -HAP (most probably through 4,4′-dihydroxy-α-methylstilbene). Furthermore, it has been also suggested that the produced p -HAP is further mineralized [ 4 , 7 , 9 , 11 , 14 , 30 , 32 ], it can explain why further metabolites of p -HAP have not been detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these harmful and toxic effects, bisphenol-A have captivated the attention of several regulatory agencies, such as the European Food Safety Authority (EFSA) who decreased the tolerable daily intake (TDI) for BA from 50 to 4 μg/kg per bodyweight day. 15 To mitigate the harmful effects of this pollutant on the environment and especially in water, several processes to remove this compound have been developed including adsorption, 16,17 electrochemical process, 18,19 chlorination, 20,21 biodegradation, [22][23][24] and advanced oxidation methods (AOP) which are based on powerful oxidants as the radical • OH. 20 However, in the case of BA chlorination and ozonation, several studies have reported the formation of toxic intermediates.…”
Section: Introductionmentioning
confidence: 99%